2004
DOI: 10.1385/ncc:1:3:347
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability and Outcome in Acute Severe Stroke: Role of Power Spectral Analysis

Abstract: HRV measurements are independent predictors of outcome in acute severe stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 15 publications
2
43
0
1
Order By: Relevance
“…These findings of altered autonomic activity with increased sympathetic activation correlate with earlier studies on ischemic stroke [6, 14, 21, 22]. The aberrant neurocardiac regulation persists even in the postacute phase [23] and abnormal heart rate dynamics has also been associated with poststroke mortality [24].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…These findings of altered autonomic activity with increased sympathetic activation correlate with earlier studies on ischemic stroke [6, 14, 21, 22]. The aberrant neurocardiac regulation persists even in the postacute phase [23] and abnormal heart rate dynamics has also been associated with poststroke mortality [24].…”
Section: Discussionsupporting
confidence: 84%
“…The resting heart rate (HR) and blood pressure (BP) recordings were carried out in the autonomic laboratory, Department of Neurophysiology, NIMHANS under standardized conditions [14, 15]. Patients were advised to abstain from alcohol and nicotine for 24 hours before evaluation.…”
Section: Methodsmentioning
confidence: 99%
“…Other than heart disorders, the heart rate signals can be used for diagnosis of diseases like diabetic neuropathies, and depression [10,[12][13][14][15]. They are cheap and can be acquired from ECG signals.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the clinical findings regarding the VLF content of heart rate variability as a predictor of cardiac health are not univocal. For instance, in post stroke patients (Gujjar et al, 2004) and in middle aged women with coronary disease (Janszky et al, 2004), the VLF spectral power positively correlates with mortality, while no relation has been found by other authors between VLF and future risk of sudden death (Björkander et al, 2009), and other studies have reported that low levels of VLF fluctuations might be associated with an adverse prognosis in patients with acute myocardial infarction (Bigger et al, 1992;Bonaduce et al, 1994;Carney et al, 2007).…”
Section: Introductionmentioning
confidence: 97%